Arahan pengembangan agribisnis buah naga di pekarangan terintegrasi desa wisata Banuroja - Dewa Oka Suparwata; Ramlan Pomolango (Fakultas Pertanian Universitas Yudharta Pasuruan, 2019)
Among the many problems, one of the obstacles to farming is the weak strategy to make up for the highest profit. The purpose of this study is to examine the direction of the development of agribusiness of dragon fruit in the integrated yard of a tourism village. This research was carried out in Banuroja Village, Randangan District, Gorontalo, from March to June 2019. This research was designed using a survey approach. The number of respondents are 58 people. The data were analyzed using the SWOT (Strength, Weakness, Opportunity, and Threat) methods. The analysis shows that SWOT awareness is in quadrant III (change strategy). The recommended strategy priorities consist of; (a) the development of dragon fruit-based agro-tourism through strengthening multicultural farmers in the promotion of rural tourism, (b) forming farmer groups in the integration of agricultural tourism management as an effort to strengthen institutions, and (c) developing super red dragon fruit in an effort to expand its development because it is much sought after by consumers.